Transrectal bladder prolapse secondary to pelvic fracture in two dogs - Crivellenti, L. Z. [UNESP]; Silveira, M. P.; Silva, A. N.; Borin-Crivellenti, S. [UNESP]; Raposo, T. M. M. [UNESP]; Honsho, D. K. (Wiley-Blackwell, 2014)
This report describes the exteriorisation of the urinary bladder in two dogs as a result of a laceration of the rectum from a traumatic pelvic fracture. Clinical examination and contrast radiography of the bladder were used as diagnostic tools. Both patients were treated with exploratory laparotomy, where traction of the bladder was utilised to pull the bladder through the traumatic rectal laceration allowing the organ to return to its normal anatomical position. This procedure was followed by surgical reconstruction of the rectum, resulting in effective resolution of each case.